Distance learning - Hayes. Lynne; Lawper Video Productions (Lawrenceveille, NJ : Meridian Education Corporation, 2000)
Introduces several types of distance learning with the features and benefits of each. Examples of real experiences are shown
Executive producer, Twila Sears
DVD Format
Keywords: Distance education